Caracterização e eficiência de diferentes meios filtrantes fibrosos na remoção de nanopartículas - Bortolassi, Ana Cláudia Canalli (Universidade Federal de São Carlos, 2015)
Human exposure to nanoparticles is increasingly becoming a concern, including in the workplace, due to urban and industrial development and the increasing use of motor vehicles. Filtration using fibrous filters is among the various options that can be used to provide efficient elimination of particles. It is known that there has been little research concerning the removal of nanoparticles using these filtration media. The aim of this study was to characterize, evaluate the efficiency and analyze the influence of filtration area on the efficiencies of the filter media HEPA (high efficiency particulate air), glass, micro-quartz, and polyester (300 g/m2) for the removal of nanoparticles. The filtration area was analyzed because is not possible in general to do the experimental testes in laboratory with large filtration area. The evaluation of the filter media depend on the structure of the filters (fiber diameter, thickness, and permeability), the operating conditions (superficial velocity and filtration area), and the characteristics of the filtered aerosols (density and size distribution). The characterization was used to evaluate the filter media and explain some results. Thickness, fiber diameter and permeability are examples of characterization parameters. The experimental setup was used in experimental tests of permeability and efficiency for the 5.3 and 40.7 cm2 filtration areas. A solution of 5 g/L sodium chloride (NaCl) was used to generate the nanoparticles in the filtration tests and a constant superficial velocity of 0.05 m/s. Particles were counted before and after passing through the filter media at the beginning of filtration using the electrical mobility technique. At the end of the filtration (one hour), the particles were again counted before and after the filters (in triplicate). The permeability constants of the HEPA, glass, and micro-quartz filters were the lower and they are influenced by the filtration area, while a much higher value was obtained for the polyester filter and showed no significant variation using different filtration area. Altogether, all the filter media were highly efficient in removing nanoparticles during approximately 2 hours of filtration, with the exception of the polyester filter, for which the efficiency decreased with increasing particle diameter.
Keywords: Filtração; Nanopartículas; Mecanismo de coleta; Meios filtrantes; Permeabilidade; Collection mechanisms; Electrical mobility; Fibrous filters; Filtration efficiency; Nanoparticle filtration; Permeability; ENGENHARIAS::ENGENHARIA QUIMICA